Metodika učenja košarkarskih iger na en koš - Erčulj, Frane (Šport (Ljubljana), 2013)
Games with one basket are basic basketball games where players learn about the essential elements of the basketball game (5:5 with two baskets) as well as systematically build up and broaden their knowledge. These games are simpler because a smaller number of players is involved; however, they are suitable for strengthening and maintaining many motor and functional abilities and they also impact significantly on the development of man's psycho-social dimensions. One can say that games with one basket positively affect the development of onećs personality and also have an important educational function. Owing to the above and the fact that many times in sports halls and also on outdoor basketball courts it is not possible to play basketball with two baskets (smaller sports halls, only one-half of the court can be used, too many children), games with one basket also represent important contents of physical education classes. The article presents the methodology for learning basketball games with one basket, some other games with adjusted rules as well as types of competitions in games with one basket.
Keywords: basketball; košarka; learning; physical education; sport; šport; športna vzgoja; training; trening; učenje